K-Means Algorithm to Group Students’ Academic Status at STMIK Palangka Raya - Rusdiana, Lili (CSRID (Computer Science Research and Its Development Journal), 2018)
As one of clustering methods K-Means algorithm can be used to group 93 data of STMIK Palangka Raya students into 3 namely pass, active, and inactive. The stages of it produce 9 iterations since the displacement of the group in which there is a movement from one group to another because the change value of the object function. The iteration can be stopped at the 9th because the value of the object function change is below the given threshold value of 0.1 and the absence of group movement in the data used. The 9 iterations that occur indicate the rise and fall the change value of object function and data transfer in the location of the group.